(3CYdGe GdfHhIs - (3YHO GdQMef Hf eMeO CHj MGJe GHf EOQjS Hf GdefPQ GdJejej GdMfXdqj GdQGRqj, CHh eMeO,J (B327 (3g` s
(3ChdgG (B:s
(3cdg ef GdGLQ Ydi Pdc eSJYjfkG dg Yf LGQg Gf jdgefi ddUhGH h GdQTGO aUd ajeG LQi Hjfi hHjf GdedMO Cfg fGXQfi ai GeQ GdfHhI s
(3BNQgG (B:s
(3hdhdG Gf Gddg Ydege deG YdehG dCg Ndb LejY GdNdGFb hYde eG XgQ heG HWf hde jTQc GMOkG ef NdbI ai GdYde HgG EdG GdfHi Udi Gddg Ydjg hSde s
(3hQbe (B29 (3JHJHYI Qbe (B23 (3ai GdJUhjQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B324 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B170s
Keywords: (3eJaQbGJs